2020
DOI: 10.3390/biom10020329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabis Use on the Protein and Lipid Profile of Olfactory Neuroepithelium Cells from Schizophrenia Patients Studied by Synchrotron-Based FTIR Spectroscopy

Abstract: Schizophrenia (SCZ) is a neurodevelopmental disorder with a high genetic component, but the presence of environmental stressors can be important for its onset and progression. Cannabis use can be a major risk factor for developing SCZ. However, despite the available data on the neurobiological underpinnings of SCZ, there is an important lack of studies in human neuronal tissue and living cells addressing the effects of cannabis in SCZ patients. In this study, we analysed the most relevant bio-macromolecular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Since the cytoskeleton is closely associated with cell membranes, the interaction of cannabis with the lipid bilayer or membrane bound enzyme systems may adversely affect the architecture of the cytoskeleton. In this sense, a recent study using SR-FTIR spectroscopy found that intracellular lipid chains are disordered in ON cells from cannabis users, the membrane displaying an altered lipid composition with a higher rate of membrane lipid renewal and peroxidation, and more proteins with β-sheet structures (Saladrigas-Manjon et al, 2020). Thus, these data strongly support the increased cell size and cytoskeletal alteration in the ON cells of cannabis users.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Since the cytoskeleton is closely associated with cell membranes, the interaction of cannabis with the lipid bilayer or membrane bound enzyme systems may adversely affect the architecture of the cytoskeleton. In this sense, a recent study using SR-FTIR spectroscopy found that intracellular lipid chains are disordered in ON cells from cannabis users, the membrane displaying an altered lipid composition with a higher rate of membrane lipid renewal and peroxidation, and more proteins with β-sheet structures (Saladrigas-Manjon et al, 2020). Thus, these data strongly support the increased cell size and cytoskeletal alteration in the ON cells of cannabis users.…”
Section: Discussionmentioning
confidence: 59%
“…In the field of cannabis, we previously showed that ON cells obtained from cannabis users exhibit changes in the cannabinoid CB1 receptor, and in serotonin 2A receptor heteromer expression and function, both of which were associated with cognitive performance (Galindo et al, 2018). Furthermore, the macromolecular profile of ON cells is also altered in cannabis users, these cells displaying a modified lipid composition, as well as an increase in DNA and histone methylation (Saladrigas-Manjon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the former was considered as a marker of lipidic character of a cellular compartment, while the ratio 2853/2870 cm −1 was linked to the extent of lipid peroxidation or, more in general, to biophysical modifications of lipidic chains composing cellular membranes [ 29 , 30 ]. In particular, the increasing of this ratio has been related to a higher acyl chain unsaturation level [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increment of β-sheet in the pellet cells of fraction 3 may be expected since this conformation is a sign of protein aggregation [ 38 ]. Indeed, a high content of β-sheets proteins in cells and tissues and the conversion from an α-helix rich protein population towards a β-sheets-rich one has been previously used as a hallmark of a pathologic status [ 31 ]. In this view, the increase of the β-structures could be correlated to a higher percentage of poor-quality spermatozoa, i.e., low motility and not viable cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation